Optimization of Perfluoropolyether-Based Gas Diffusion Media Preparation for PEM Fuel Cells - Riccardo Balzarotti (Energies, 2020)
A hydrophobic perfluoropolyether (PFPE)-based polymer, namely Fluorolink® P56, was studied instead of the commonly used polytetrafluoroethylene (PTFE), in order to enhance gas diffusion media (GDM) water management behavior, on the basis of a previous work in which such polymers had already proved to be superior. In particular, an attempt to optimize the GDM production procedure and to improve the microporous layer (MPL) adhesion to the substrate was carried out. Materials properties have been correlated with production routes by means of both physical characterization and electrochemical tests. The latter were performed in a single PEM fuel cell, at different relative humidity (namely 80% on anode side and 60%/100% on cathode side) and temperature (60 °C and 80 °C) conditions. Additionally, electrochemical impedance spectroscopy measurements were performed in order to assess MPLs properties and to determine the influence of production procedure on cell electrochemical parameters. The durability of the best performing sample was also evaluated and compared to a previously developed benchmark. It was found that a final dipping step into PFPE-based dispersion, following MPL deposition, seems to improve the adhesion of the MPL to the macro-porous substrate and to reduce diffusive limitations during fuel cell operation.